INNOVATIVE OPPORTUNITIES OF A CREATIVE APPROACH IN DEVELOPING PROFESSIONAL SKILLS OF FUTURE TEACHERS (The Conference Hub, 2025)
This article analyzes the conceptual model and practical aspects of the mechanism for developing the professional skills of future teachers through a creative approach. The mechanism, which integrates creative methods, interactive teaching techniques, and innovative technologies, serves to make the educational process more student-centered and creative. The article highlights the role of creative approaches in forming professional skills such as creative thinking, problem-solving, and independent decision-making. Based on both national and international pedagogical experiences, directions for the effective application of this approach in pedagogical practice are identified.